Planning of Kyiv development: historical-geographical aspects - Стеблецька, Ю. (Київський національний університет імені Тараса Шевченка, 2014)
Considered the essence of the concept “master plan” of cities, its structure and role in urban development. Distinguished historical and urban planning stages of planning of spatial development of Kyiv. In detail analyzed master plans of Kyiv in every historical and urban planning stage. Determined the main characteristic features of master plans of Kyiv in every historical and urban planning stage. Explored changing of ideas about the “capital city”. Generalized the processes of spatial development of Kyiv. Determined the prevailing scheme of city planning embedded in the master plans in the context of historical and urban planning stages.

Розглянуто сутність поняття “генеральний план” міста, його структуру та роль в розвитку міст. Виділено історико-містобудівні етапи планування просторового розвитку м. Києва. Детально проаналізовано генеральні плани м. Києва кожного історико-містобудівного етапу. Визначено основні характерні ознаки генеральних планів м. Києва, для всіх історико-містобудівних етапів. Досліджено зміну уявлень про “столичне місто”. Узагальнено процеси просторового розвитку м. Києва та визначено переважаючу схему планування міста, закладену в генпланах в розрізі історико-містобудівних етапів.
Планування розвитку м. Києва: історико-географічні аспекти
Bilokon’ Yu. M Rehional’ne planuvannya (teoriya y praktyka) [Regional planning (theory and practice)], Kyiv, 2003. Druh O. Vulytsyamy Staroho Kyyeva [The streets of Old Kyiv], L’viv, 2013. Golubkov V.M. (eds.) Kyiv. Ukraїns’ka Radjans’ka Socіalіstichna Respublіka [Kyiv. Ukrainian Soviet Socialist Republic], URE: Golovna redakcіja, Kyiv, 1965. Klyushnychenko Ye. Sotsial’no-ekonomichni osnovy planuvannya ta zabudovy mist [Socio-economic foundations of planning and urban development], Kyiv, 1999. Pistun N.D., Peresekin V.N., Mizhega N.Ja. Ekonomiko-geograficheskij kompleks krupnogo goroda (na primere g. Kieva) [Economic and geographic range of a large city (for example, in Kiev)], Kyiv, 1989. Istoriya kul’tury Ukrayiny [Cultural History of Ukraine], Available at: subject.com.ua Ofitsiynyy sayt Departamentu mistobuduvannya ta arkhitektury Kyyivs’koyi mis’koyi derzhavnoyi administratsiyi [The official website of the Department of planning and architecture of Kyiv City State Administration], Available at: http://kga.gov.ua/index.php Ofitsiynyy sayt DP «Instytut Heneral’noho planu m. Kyyeva» AT «Kyyivproekt» [Official site of “Institute of General Plan. Kyiv” “Kyivproject”], Available at: http://genplan.kiev.ua/inst.htm Pankova Ye. Turystychne krayeznavstvo [Travel country studies], Available at: www.geografica.net.ua Slyudikova T. Zabudova i blahoustriy m. Kyyeva v XIX–XX st.(za dokumentamy kyyivs’kykh derzharkhiviv) [Buildings and landscaping Kyiv in XIX-XX centuries], Available at: www.archives.gov.ua
Keywords: місто; генеральний план; планувальна структура; функціональне зонування; master plan of a city; planning structure; functional zoning